IMPROVING STUDENTS™ ACHIEVEMENT IN WRITING NARRATIVE TEXT BY USING THINK PAIR SHARE STRATEGY - Pardosi, Putri Sri Rezeki; -, Bachtiar (TRANSFORM: Journal of English Language Teaching and Learning, 2013)
ABSTRACT This study was focused to improve students™ achievement in writing narrative text by using Think Pair Share Strategy. It was conducted by applying Classroom Action Research with two cycles and six meetings. The subject of this study is Grade X Students of SMA PAB 1 MEDAN ESTATE and consisted of 28 students. The instruments for collecting data used writing test for quantitative and used diary notes, observation sheet and interview sheet for qualitative data. The mean of the test shows the improvement of the students™ score from the first test to the third test. The mean of the students™ score for orientation test was (76,7), the mean in cycle I test was (78,3), and the mean in the cycle II test was (79,4). Based on the data above, it can be concluded that Think Pair Share Strategy is significantly improved students™ writing achievement especially in narrative text.